2021
DOI: 10.3390/pathogens10060635
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Presence of SARS CoV-2 in Free-Living and Captive Animals

Abstract: Due to SARS CoV-2 recombination rates, number of infected people and recent reports of environmental contamination, the possibility of SARS CoV-2 transmission to animals can be expected. We tested samples of dominant free-living and captive wildlife species in Croatia for the presence of anti-SARS CoV-2 antibodies and viral RNA. In total, from June 2020 until February 2021, we tested blood, muscle extract and fecal samples of 422 free-living wild boars (Sus scrofa), red foxes (Vulpes vulpes) and jackals (Canis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 56 publications
(78 reference statements)
3
34
0
Order By: Relevance
“…Even though SARS-CoV-2 RNA was detected in open surface waters ( Kolarević et al, 2021 ; Mahlknecht et al, 2021 ; Rimoldi et al, 2020 ), there is no evidence for a transmission of SARS-CoV-2 via water-food-environmental media ( Adelodun et al, 2021 ). To this date SARS-CoV-2 pandemic strain was not detected to circulate in free-ranging wildlife species which may be in contact with surface waters, wastewaters and human waste in general ( Colombo et al, 2021 ; Jemeršić et al, 2021 ). However, wastewater discharge, primarily those untreated, is the source of contamination for aquatic environments ( Bosch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though SARS-CoV-2 RNA was detected in open surface waters ( Kolarević et al, 2021 ; Mahlknecht et al, 2021 ; Rimoldi et al, 2020 ), there is no evidence for a transmission of SARS-CoV-2 via water-food-environmental media ( Adelodun et al, 2021 ). To this date SARS-CoV-2 pandemic strain was not detected to circulate in free-ranging wildlife species which may be in contact with surface waters, wastewaters and human waste in general ( Colombo et al, 2021 ; Jemeršić et al, 2021 ). However, wastewater discharge, primarily those untreated, is the source of contamination for aquatic environments ( Bosch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some blood samples and muscle extracts gave positive ELISA results, all tested negative by surrogate VNT. The same was true for the RT-PCR results, and none of the fecal samples tested positive, giving no evidence of spillover of SARS-CoV-2 to free-living or captive wild animals [37]. June-November 2020 204 6 (2.9) 1.0-6.2 0 (0) 0-1.8 * 0 (0)…”
Section: Covid-19 In Wildlifementioning
confidence: 56%
“…SARS-CoV-2 RNA detection rates varied from 0% to 37.5%. Most of the Ct values were ≥30 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), which assumes a low viral load. The investigation confirmed that 9/15 (60.0%) of the tested locations were contaminated with SARS-CoV-2, with one or more positive samples per location.…”
Section: Sars-cov-2 In Households With Covid-19 Casesmentioning
confidence: 99%
“…In Croatia, jackals (Canis aureus), free-living wild boars (Sus scrofa), and red foxes (Vulpes vulpes) showed positive antibody response to SARS-CoV-2 using ELISA. However, the virus neutralization test's positive conclusions were not verified [152]. However, chickens, geese, and pigs were found to be nonsusceptible hosts for SARS-CoV-2 [153][154][155].…”
Section: Sars-cov-2 In Other Animalsmentioning
confidence: 97%